ANALYSIS OF STRATEGIES FOR REDUCING STUNTING RATES IN SOUTHEAST ACEH DISTRICT IN 2021 - Bahrul Ilmi (CV Naskah Aceh, 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. Stunting affects the growth and development of the brain. Stunted children also have a higher risk of suffering from chronic diseases in their adult years. In fact, stunting and malnutrition are estimated to contribute to a reduction of 2-3% of Gross Domestic Product (GDP) each year. Based on the results of the 2021 Indonesian Nutrition Status Survey (SSGI) conducted by the Ministry of Health, the stunting prevalence rate in Indonesia in 2021 was 24.4%, or a decrease of 6.4% from 30.8% in 2018 and shows the prevalence of stunting under five in Indonesia still high above the limit set by WHO (20%). In 2015, Indonesia was the second highest after Laos for the number of stunted children. Basic Health Research Data (Riskesdas) shows that the prevalence of stunting under five in 2018 reached 30.8 percent, which means that one in three under five is stunted. Indonesia itself, he said, is a country with the 2nd highest child stunting burden in the Southeast Asian Region and 5th in the world. The government has a target of reducing the prevalence to 14% in 2024. That means, Indonesia must reduce the prevalence by 10.4% in the next 2.5 years, which of course is a challenge for all parties to achieve it.vTo achieve the government's target , of course Of course, there must be support from every province or district and so on. From the 2021 Indonesian Nutrition Status Study (SSGI) data, Aceh occupies the third highest position after East Nusa Tenggara (NTT) and West Sulawesi in first and second positions. Gayo Lues Regency is the area with the highest stunting prevalence, 42.9 percent, followed by Subulussalam City with 41.8 percent. Meanwhile, Banda Aceh City (23.4%) and Sabang City (23.8%) were the areas with the lowest prevalence. Based on the results of the 2021 Indonesian Nutrition Status Study (SSGI) BKKBN Aceh, the Stunting rate for Southeast Aceh District is at 34.1 percent, placing this area in the top 8 at the district / city level throughout Aceh. This figure still exceeds the Aceh provincial average which is only 33.2 percent.